Innovation and less harmful alternatives to tobacco: The case of nicotine pouches regulation - Christofer Fjellner (European Centre for International Political Economy (ECIPE), 2020)
The market for tobacco or tobacco-like products is changing fast. Consumers are increasingly motivated to substitute classic cigarettes with products that are less damaging to health. The COVID-19 crisis, and the growing evidence from the World Health Organisation (WHO) and others that smoking increases the risk of dying from COVID-19, is likely to increase that trend. Alongside measures to reduce tobacco consumption, public-health authorities in some countries have also been at the vanguard of pushing product substitution. There is also vibrant innovation in the market with old and new firms coming up with new products that reduce the harm of tobacco consumption. E-cigarettes are one among such products. A less known example is nicotine pouches. For some years now, tobacco-free nicotine pouches - a tobacco-free version of pre-portioned snus - have been available on the Swedish market. Although the use of the product is increasing and is marketed outside Europe, nicotine pouches are not subject to any specific product regulation - neither in Europe nor elsewhere. That makes the product unique because similar products are regulated in both international treaties and national legislation. It is a matter of time before nicotine pouches will get regulated and the purpose of this report is to provide an analysis of different regulatory approaches and what they entail. This is chiefly done by observing key trends in tobacco-prevention policies and analyzing how the regulation of similar products has developed over time. Because of their product-specific similarities, the reference products for the analysis are snus and e-cigarettes. Obviously, these similarities include aspects of their harm-reduction potential (when compared to cigarettes) but also factors such as nicotine dependence, number of users, and the specifics of their regulation. The analysis is particularly focused on the regulation of these products in Europe and North America, and also takes stock of the factors that shaped the debate and affected the outcome of these regulations. Consideration is also given to the possibility that new conflicts may emerge in the wake of the increased use of nicotine pouches and how this may affect future regulation. In light of this analysis, the report provides a scenario for the regulation of nicotine pouches.
Keywords: 330